A possible new oxidation marker for hair adulteration: Detection of PTeCA (1H‐pyrrole‐2, 3, 4, 5‐tetracarboxylic acid) in bleached hair. Issue 2 (27th December 2019) - Eisenbeiss, Lisa; Binz, Tina M.; Baumgartner, Markus R.; Steuer, Andrea E.; Kraemer, Thomas
Abstract: Hair analysis has become a valuable tool in forensic toxicology to assess drug or alcohol abstinence. Yet, hair adulteration by cosmetic products presents a major challenge for forensic hair analysis. Oxidative treatments, e.g. bleaching, may lead to analyte loss and thereby to false negative results. Currently, the eumelanin degradation product 1H‐pyrrole‐2, 3, 5‐tricarboxylic acid (PTCA) serves as a marker for oxidative hair treatment, but requires the definition of cut‐off values. To investigate further eumelanin degradation products as markers for oxidative hair treatment, hair samples with and without in vitro bleaching (hydrogen peroxide (H2 O2 ) concentrations 1.9% up to 12%; incubation times 15 min, 30 min, 60 min) were analyzed by liquid chromatography coupled to high‐resolution time of flight mass spectrometry (HPLC‐HRMS). The distribution of eumelanin degradation products along the hair shaft was investigated for routine applicability after segmentation of cosmetically untreated hair samples and authentically treated hair samples. The signals of the eumelanin degradation products PTCA, 1H‐pyrrole‐2, 3, 4‐tricarboxylic acid (isoPTCA), and 1H‐pyrrole‐2, 3, 4, 5‐tetracarboxylic acid (PTeCA) were found to be significantly elevated after in vitro bleaching already with low H2 O2 concentrations and after short incubation times. In contrast to PTCA and isoPTCA, PTeCA was not detectable in cosmetically untreated segments up to 12 cm from hair root and was only formed through the oxidation process. The results of the study show that the detection of PTeCA within the proximal 3 to 6 cm segment can be applied to reliably detect hair adulteration attempts through hair bleaching. Abstract : The eumelanin degradation product 1H‐pyrrole‐2, 3, 4, 5‐tetracarboxylic acid (PTeCA) was formed after in vitro bleaching of hair samples. Detection of PTeCA in hair samples provides a strong indication of oxidative hair treatment without necessitating cut‐off values.